Implementation of Land Reforms A Review by the Land Reforms Implementation Committee of the National Development Council - Planning Commission (Planning Commission, 1966)
In November. 1963, following the Mid-term Appraisal of the Third Plan, the National Development Council reviewed the progress made in the implementation of land reforms in different States and noted that on account of legal and Other factors, in some States, the legislation had not been fully enforced. The National Development Council emphasised that speedy execution of the programme of land reforms was vital for increasing agricultural production and strengthening the rural economy and called upon all the State Governments to complete the implementation of land reform programmes before the end of the Third Plan.
Planning Commission
Planning Commission